The purchasing power parity puzzle: An update - Weshah A. Razzak (Economics and Econometrics Research Institute (EERI), 2018)
We show that the Purchasing Power Parity (PPP) puzzle, whereby the half-life of the shock to the real exchange rate is long and unjustifiable by monetary and financial shocks, is a result of specification and estimation issues. We provide an alternative specification for PPP and show that the half-life of the shock could be as short as 6.8 months and as long as 2 years, which is considerably shorter than what have been reported in the literature.
Keywords: C13; C18; F31; 330; PPP; unit root; half-life of shocks